La construction d’images publiques dans le discours politique médiatique. - Olivier Turbide (Communiquer)
Analysing self-presentation strategies in political broadcast talk from an interactionnist perspective, this article present some analytical tools to evaluate communication performance effectiveness. This analytical framework is illustrated by examples drawn from a news interview during 2003 Quebec political campaign. The analysis reveals that successful self-presentation is based on politicians’ communication ability to fine-tune their performance according the way the interaction is built turn by turn in situ and to play with the limits of what is socially allowed by the interview as a genre.